2015
DOI: 10.1007/s00601-015-1017-5
|View full text |Cite
|
Sign up to set email alerts
|

Slightly Imbalanced System of a Few Attractive Fermions in a One-Dimensional Harmonic Trap

Abstract: The ground-state properties of the two-flavored mixture of a few attractive fermions confined in a onedimensional harmonic trap is studied. It is shown that for slightly imbalanced system the pairing between fermions of opposite spins has completely different features that in the balanced case. The fraction of correlated pairs is suppressed by the presence of additional particle and another uncorrelated two-body orbital dominates in the ground-state of the system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Recently, the method has been successfully used for equal mass fermions confined in a harmonic trap [13,62,63] as well as for fermions of different masses [42]. First we decompose the field operatorsΨ σ (x) into the basis of the eigenfunctions of the corresponding single-particle Hamiltonians…”
Section: Exact Diagonalization Approachmentioning
confidence: 99%
“…Recently, the method has been successfully used for equal mass fermions confined in a harmonic trap [13,62,63] as well as for fermions of different masses [42]. First we decompose the field operatorsΨ σ (x) into the basis of the eigenfunctions of the corresponding single-particle Hamiltonians…”
Section: Exact Diagonalization Approachmentioning
confidence: 99%
“…Tunneling experiments in the few-body limit demonstrated single-atom control [6,7]. One has already observed the formation of a Fermi sea [8], as well as pair correlations in onedimensional (1D) few-body atomic gases [5] that have also been studied extensively theoretically [9][10][11][12][13]. The few-to many-body transition is arguably even more interesting in higher dimensions, where quantum phase transitions with varying degrees of broken symmetry are ubiquitous [14].…”
mentioning
confidence: 99%
“…is the angular momentum. This method has been extensively applied to attractive fermion systems, mainly in 1D [9][10][11][12][13] but also in 2D [31,32] Using a sparse representation of the resulting matrix, we find the eigenvectors using the implicitly restarted Arnoldi iteration method [36]. This generally allows for a significantly larger number of basis states, ∼ 10 7 , as compared to other available diagonalisation methods, which is crucial, since we need a very large basis set for an accurate calculation of the low-lying collective modes.…”
mentioning
confidence: 99%
“…Quite a different approach to imbalanced fermionic mixtures was presented in [305], where systems with additional unpaired fermion were analyzed. Based on a description in the language of the reduced two-particle density matrix, it was shown that in the case studied, the pairing between fermions of opposite spins has completely different features that in the balanced case.…”
Section: H Attractive Forcesmentioning
confidence: 99%